2013
DOI: 10.1177/0022002713492636
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation and the Cultivation of Political Tolerance

Abstract: The goal of the current project is to integrate psychological research on emotion regulation with the study of democratic practices in general and political intolerance in particular. We hypothesized that the use of a well-established emotion regulation strategy, cognitive reappraisal, would be associated with lower levels of group-based negative emotions toward one’s least-liked group and lower levels of political intolerance toward that group. Preliminary data based on nationwide survey conducted among Jews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 44 publications
3
70
0
1
Order By: Relevance
“…For example, building on the vast literature of cognitive reappraisal (Gross 2008), found that participants who were taught how to better regulate their emotions using cognitive reappraisal, expressed less anger following a real and dramatic event in the history of the Israeli-Palestinian conflict. As a consequence, they were also more supportive of conciliatory policies toward Palestinians both one week and five months after the training had taken place (see also Halperin et al 2014).…”
Section: Skill Training Interventionsmentioning
confidence: 99%
“…For example, building on the vast literature of cognitive reappraisal (Gross 2008), found that participants who were taught how to better regulate their emotions using cognitive reappraisal, expressed less anger following a real and dramatic event in the history of the Israeli-Palestinian conflict. As a consequence, they were also more supportive of conciliatory policies toward Palestinians both one week and five months after the training had taken place (see also Halperin et al 2014).…”
Section: Skill Training Interventionsmentioning
confidence: 99%
“…Importantly, people can regulate their emotions in both individual (e.g., Gross, 2007;Gross, Richards, & John, 2006) and in group contexts (e.g., Halperin, Pliskin, Saguy, Liberman, & Gross, 2014;Halperin, Porat, Tamir, & Gross, 2013).…”
Section: The Instrumental Approach To Emotion Regulationmentioning
confidence: 99%
“…For example, these studies show that by employing well-established methods of emotion regulation, previously tested only on the personal level, group-based emotions may be changed as well, consequently infl uencing intergroup attitudes (e.g., Halperin et al 2014 ). More importantly, it appears that teaching people how to regulate their emotions using such strategies may increase their willingness to compromise for peace even several months after the initial intervention Halperin et al 2013 ).…”
Section: Unfreezing Processmentioning
confidence: 99%